2003
DOI: 10.1093/bja/aeg123
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal isobaric bupivacaine–morphine and ropivacaine–morphine for Caesarean delivery † †Presented at the 2nd World Congress of the World Institute of Pain, I˙stanbul, Turkey, June 2001.

Abstract: Intrathecal isobaric ropivacaine 0.5% 15 mg plus morphine 150 micro g provides sufficient anaesthesia for Caesarean delivery. The ropivacaine-morphine combination resulted in shorter motor block, similar sensory and postoperative analgesia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…Ogun et al [19] found that intrathecal isobaric ropivacaine 0.5% 15 mg with morphine 150 µg provided sufficient anaesthesia for caesarean delivery. The parturients were compared with the bupivacaine group.…”
Section: Discussionmentioning
confidence: 99%
“…Ogun et al [19] found that intrathecal isobaric ropivacaine 0.5% 15 mg with morphine 150 µg provided sufficient anaesthesia for caesarean delivery. The parturients were compared with the bupivacaine group.…”
Section: Discussionmentioning
confidence: 99%
“…The median dosage of 0.5% Hyperbaric Bupivacaine was significantly low of 9(8.5-9.5 [7.5-11])mg in CD group in comparison to 11 mg in FD group. The median time to reach T6 sensory block 2(2-3[1-6]) minutes in Group FD was much early in comparison to 4(3-5) [1][2][3][4][5][6][7][8][9][10][11][12]) minutes in Group CD. The median maximum sensory level achieved in 20 minutes T3(T3-T4[T2-T5]) in Group FD was also significant in comparison to T5(T4-T5[T3-T5]).…”
Section: Figure 1: Consort Flow Diagrammentioning
confidence: 99%
“…The values are statistically significant with p-value <0.05. The median time to motor blockage Bromage-III was relatively early 4(3-6 [1][2][3][4][5][6][7][8][9][10][11][12])minutes in Group FD in comparison to 6(5-8 [2][3][4][5][6][7][8][9][10][11][12][13][14]) minutes in Group CD with a p-value of <0.05. Two parturient (4.5%) in Group CD needed head down position in order to get the desired level of sensory block.…”
Section: Figure 1: Consort Flow Diagrammentioning
confidence: 99%
See 2 more Smart Citations